Mycobacterium tuberculosis Uses Mce Proteins to Interfere With Host Cell Signaling - Fenn, Katherine; Wong, Chi Tung; Darbari, Vidya Chandran (Frontiers in Molecular Biosciences, 2020)
Tuberculosis continues to be the main cause of mortality by an infectious agent, making M. tuberculosis one of the most successful pathogens to survive for long durations within human cells. In order to survive against host defenses, Mycobacterium tuberculosis modulates host cell signalling. It employs many proteins to achieve this and the Mce proteins are emerging as one group that plays a role in host cell signalling in addition to their primary role as lipid/sterol transporters. Mce proteins belong to the conserved Mce/MlaD superfamily ubiquitous in diderm bacteria and chloroplasts. In mycobacteria, Mce operons, encode for six different Mce proteins that assemble with inner membrane permeases into complexes that span across the mycobacterial cell wall. Their involvement in signalling modulation is varied and they have been shown to bind ERK1/2 to alter host cytokine expression; eEF1A1 to promote host cell proliferation and integrins for host cell adherence and entry. Recently, structures of prokaryotic Mce/MlaD proteins have been determined, giving an insight into the conserved domain. In this mini-review, we discuss the current evidence for the role of mycobacterial Mce proteins in host cell signalling and structural characteristics of the protein-protein interactions coordinated by the human proteins to modulate the host signalling.